2018
DOI: 10.1371/journal.pone.0206481
|View full text |Cite
|
Sign up to set email alerts
|

Scaled traumatic brain injury results in unique metabolomic signatures between gray matter, white matter, and serum in a piglet model

Abstract: Traumatic brain injury (TBI) is a leading cause of death and long-term disability in the United States. The heterogeneity of the disease coupled with the lack of comprehensive, standardized scales to adequately characterize multiple types of TBI remain to be major challenges facing effective therapeutic development. A systems level approach to TBI diagnosis through the use of metabolomics could lead to a better understanding of cellular changes post-TBI and potential therapeutic targets. In the current study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Serine, on the other hand, has been suggested to play an essential role in the function of the central nervous system 55 and disruption in the metabolism of glycine, serine and threonine might affect neuroprotection and normal function of the nervous system 56 . In a piglet model of TBI, similar changes in amino acid levels were observed in brain tissue, with different responses occurring in gray and white matter across all injury severities 57 . It is also plausible that decreased amino acid concentrations may reflect both increased protein catabolism associated with acute illness 58 , and increased use of these metabolites for energy substrates in the body.…”
Section: Discussionmentioning
confidence: 72%
“…Serine, on the other hand, has been suggested to play an essential role in the function of the central nervous system 55 and disruption in the metabolism of glycine, serine and threonine might affect neuroprotection and normal function of the nervous system 56 . In a piglet model of TBI, similar changes in amino acid levels were observed in brain tissue, with different responses occurring in gray and white matter across all injury severities 57 . It is also plausible that decreased amino acid concentrations may reflect both increased protein catabolism associated with acute illness 58 , and increased use of these metabolites for energy substrates in the body.…”
Section: Discussionmentioning
confidence: 72%
“…Plasma PC was not altered 1 hour after lateral fluid percussion in rats, although changes in brain PC were identified [70]. In a pig TBI model, serum PL metabolism was altered 24 hours post-CCI, but no longer at 7 days [71].…”
Section: Phospholipidsmentioning
confidence: 89%
“…Previous studies have presented changes in the levels of various metabolites within the damaged hemispheres of experimental TBI animals ( Baker et al., 2018 ; Chitturi et al., 2018 ; Harris et al., 2012 ; McGuire et al., 2019 ). In this study, we observed changes in the levels of a sufficient number of metabolites to suggest how normal metabolic pathways have been disturbed and result in alternative metabolic pathways not previously described within the context of TBI.…”
Section: Discussionmentioning
confidence: 99%